Childcare and Women’s Labor Market Outcomes in Lower-and Middle-Income Countries : A Policy Brief - Halim, Daniel; Perova, Elizaveta; Reynolds, Sarah (World Bank, Washington, DC, 2022)
Twenty-two studies from lower- and middle-income countries rigorously tested if an increase in access to childcare improved mothers’ labor force participation or earnings. All but one study found at least some positive impact on mothers’ labor force participation and related outcomes resulting from access to care, an increase in care hours, or a reduction in the cost of care. The results of this review are encouraging; childcare can help improve female labor market outcomes in low- and middle-income countries.